2010
DOI: 10.1002/ana.22005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of vision and retinal nerve fiber layer thickness in multiple sclerosis

Abstract: Objective-Cross-sectional studies of optical coherence tomography (OCT) show that retinal nerve fiber layer (RNFL) thickness is reduced in multiple sclerosis (MS) and correlates with visual function. We determined how longitudinal changes in RNFL thickness relate to visual loss. We also examined patterns of RNFL thinning over time in MS eyes with and without a prior history of acute optic neuritis (ON).Methods-Patients underwent OCT measurement of RNFL thickness at baseline and at 6-month intervals during a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
318
2
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 341 publications
(357 citation statements)
references
References 51 publications
29
318
2
8
Order By: Relevance
“…The individual relationship between RGC neuroaxonal loss or VEP latency delay with worsening LCVA has been demonstrated previously 14, 15, 24, 27, 38, 39. However, the associations found in our study were generally stronger, possibly due to the use of asymmetry analysis, which eliminates the effect of intersubject variability.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The individual relationship between RGC neuroaxonal loss or VEP latency delay with worsening LCVA has been demonstrated previously 14, 15, 24, 27, 38, 39. However, the associations found in our study were generally stronger, possibly due to the use of asymmetry analysis, which eliminates the effect of intersubject variability.…”
Section: Discussionmentioning
confidence: 57%
“…OCT measurement of inner retinal layers (including the retinal nerve fiber layer (RNFL) has been validated as an accurate measure on axonal loss in anterior visual pathway and has been extensively applied to the investigation of MS 14, 15, 16, 17, 18. Thinning of the RNFL identifies retrograde axonal degeneration following damage to the optic nerve or the optic tract, providing an opportunity to quantitatively assess axonal damage associated with ON.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the MS patients in our cohort had a mean annual rate of average RNFL change of À1.17 (95% CI: À2.27 to 4.74) similar to the results reported in previous studies. 10,11 In conclusion, ON might be present in subclinical (occult) form without typical symptoms or complains. 32,33 Our patients did not have any complaints, especially visual, during the follow-up period and had not been examined by OCT or another technique for early detection of subclinical optic neuritis in the inter-observational period.…”
Section: Discussionmentioning
confidence: 92%
“…10,16 Talman et al reported progressive RNFL thinning in some patients with MS, even in the absence of ON, during a mean follow-up of 18 months in 299 patients. 10 Another study, which investigated a large cohort of MS patients and healthy controls during a 2-year follow-up, reported greater decreases of RNFL thickness in the MS patients, but statistical differences were found only for the average RNFL thickness and not for other measures such as superior and inferior RNFL. 16 Different studies have reported progressive, agerelated decline of RNFL and macular thicknesses in healthy subjects determined by OCT or other non-invasive imaging in cross-sectional and longitudinal studies during short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation